Financial Performance Determinants in Indonesian Banking: The Role of Credit Risk and Bank-Specific Factors - Dim Zarita Suryanugraha; Galih Nugraha; Dodi Tirtana; Tine Badriatin; Ana Sakinatun Nisa (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
Purpose: This study examines the effects of credit risk and bank-specific factors on the financial performance of Indonesian banks, particularly Bank Groups Based on Core Capital (Kelompok Bank Berdasarkan Modal Inti/KBMI) 3 and 4, and addresses inconsistent findings in previous studies on bank profitability. Methodology: The study employs panel data from 13 commercial banks listed on the Indonesia Stock Exchange during 2015–2024, yielding 130 observations. Financial performance is measured by Return on Assets (ROA), while credit risk is proxied by Non-Performing Loans (NPL). Bank-specific factors include Loan-to-Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO), Net Interest Margin (NIM), and Current Account Saving Account (CASA). The Random Effects Model (REM) with White cross-section standard errors is used for estimation. Findings: NPL and BOPO have significant negative effects on ROA, while LDR and NIM positively and significantly affect ROA. CASA has an insignificant effect on ROA. Novelty: This study provides evidence from large Indonesian banks and shows that operational efficiency and interest margin management are more important drivers of profitability than low-cost funding accumulation, offering implications for bank management and policymakers.